PEMEROLEHAN SEMANTIK PADA ANAK USIA 7 TAHUN DI MADRASAH IBTIDAIAH NEGERI 1 KOTA SINGKAWANG - Anggraeni, Viola Nur Apriananda; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe objective of this research is to motivated the reader to see the vocabulary development produced by a child in interpreting the vocabulary, word classes, semantic relations produced by 7-year-old children, inflation and contraction of meaning. The method of this research is descriptive method. The form of this research is qualitative. The source of data in this research is 7 years old students of 2B. The data in this research were words, phrases, and sentences produced from 7 years old children. Technique of data collection in this research were tapping technique, able to see and engage listening proficiency, recording technique, note taking technique, and drawing technique. The technique and methods of data analysis in this research were the equivalent method and use marking reading technique. The method and technique of presenting the results of data analysis in this research were formal and informal methods while the data presentation technique used table. Based on the results, it can be concluded that in the vocabulary acquisition, there are 14 groups of lexicon acquisition, 9 word classes, 6 semantic relations, 9 semantic feature classifications, 13 nouns that inflate in meaning and 9 nouns that shrink in meaning. Â Keywords: Inflating and Shrinking the meaning, Retviring Vocabulary, Semantics Relations, Word Class.Â